Data on carbon concentrations of adaptation experiment - Andersson, Martin (Uppsala University, 2018)
The dataset was originally published in DiVA and moved to SND in 2024.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on carbon concentrations of adaptation experiment
Carbon concentrations of adaptation experiment
Keywords: concentration; koncentrering; environmental microbiology; miljömikrobiologi; microbiology; mikrobiologi; carbon dioxide; koldioxid; Microbiology; Mikrobiologi